Modelling approaches for climate risk and adaptation in the context of sustainable intensification - Diancoumba, Madina; Akinseye, Folorunso M.; Faye, Awa; Emanuel, Joseph Jacob; Webber, Heidi; Faye, Aliou; Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
From September 11th to 17th 2022, was held at the Centre d’étude régional pour l’amélioration de l’adaptation à la sécheresse (CERAAS), Thiès Escale, Senegal, an international summer school (summer school CMRA 2022) organized by the Leibniz Centre for Agricultural Landscape Research (ZALF) in collaboration with the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) and the International Livestock research Institute (ILRI). With the financial and technical supports of Volkswagen Foundation and AICCRA project, this summer school equiped the West Africa’s next-generation agricultural researchers and policymakers to use modeling tools to accelerate decision-making in addressing climate risks and sustainable intensification. A total of 32 participants from across European, Asian and African institutions that have different background were convened. The summer school was designed to provide Master, doctoral and postdoc scholars with a broad overview of the system’s analysis, best practices in model application climate change impact assessments, as well as emerging applications and challenges for crop modeling to support sustainable intensification of smallholder farming systems. The participants were equipped with the knowledge and skills to use crop models in the design and evaluation of resilient and productive cropping systems.